Cationic lipid-assisted nanoparticles for simultaneous delivery of CD47 siRNA and R848 to promote antitumor immune responses - Li, Simin; Chen, Yichang; Ma, Ruolin; Du, Ye; Han, Bing (Frontiers in Pharmacology, 2023)
Triple negative breast cancer (TNBC) usually has a poor prognosis. Although the immunotherapy of triple negative breast cancer (TNBC) has achieved great progress, only a few patients can benefit from the current treatment. CD47 is widely expressed on the surface of TNBC cells and may become an immune checkpoint for TNBC treatment. Nevertheless, there has been increasingly more attention to systemic side effect since the ubiquitous expression of CD47 on normal cells. Toll-like receptors (TLRs) agonist resiquimod (R848) can activate dendritic cells (DCs) and promote the maturation of immune cells in tumor microenvironment, which further enhanced the tumor inhibition ability of immune system and synergize with CD47 small interfering RNA (siRNA) for TNBC therapy. In order to improve efficacy and reduce toxicity, R848 and siCD47 were entrapped into amphiphilic PEG-PLGA nanoparticles by double emulsification and stable nanoparticles NP/R848/siCD47 was generated to investigate their anti-tumor effects in a TNBC tumor-bearing mouse model. Here we show that PEG-PLGA nanoparticles are effective nano carrier which can safely and effectively deliver siCD47 and R848 to tumor tissue as demonstrated by retarded tumor growth. Mechanistically, downregulation of CD47 expression and activation of DCs took part in promoting the immune response of cytotoxic T cells (CTLs). Meanwhile, decrease of myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs) indicated the modulating of tumor immune microenvironment. Collectively, our findings could lay the groundwork for future therapeutic strategies of TNBC. (Fig. 5 Graphical abstract)